Pengaruh Sistem Desentralisasi Dan Ketidakpastian Lingkungan Terhadap Kinerja Manajerial Yang Dimoderasi Oleh Asimetri Informasi: Kata Kunci: Sistem Desentralisasi, Ketidakpastian Lingkungan, Kinerja Manajerial, Asimetri Informasi - Merna Merna (Jurnal Akuntansi, 2020)
The purpose of this study was to examine and analyze the influence of decentralization systems and environmental uncertainty on managerial performance. This study also examine and analyze the role of information asymmetry as a moderating variable in the relationship between the effect of decentralization systems and environmental uncertainty on managerial performance. The population of this study is the banking industry in the city of Jakarta. The sample of this research is employees with upper level heads in private banking companies listed on the Indonesia Stock Exchange. This study uses quantitative methods using the type of research carried out with quantitative data. Data is collected by sending questionnaires. The questionnaires sent were 150 questionnaires and the number returned and could be used in this study as many as 109 questionnaires. The results of this study indicate that: (i) The decentralized system has a positive effect on the company's managerial performance; (ii) Environmental uncertainty has a positive effect on company managerial performance; (iii) Information asymmetry strengthens the relationship between decentralized systems and company managerial performance; and (iv) Information asymmetry weakens the relationship between environmental uncertainty and company managerial performance. Suggestions for future research, that can use research population from other sector industries in the Indonesia Stock Exchange in addition to the banking sector. This research has a contribution to company management to pay attention to managerial performance so that the company gets better results. Keywords: decentralization system, environmental uncertainty, managerial performance, Information asymmetry